A randomized, double-blind, parallel-group phase I study comparing the pharmacokinetics, safety, and immunogenicity of LY01008, a candidate bevacizumab biosimilar, with its reference product Avastin® in healthy Chinese male subjects. (1st February 2022) - Zhou, Renpeng; Yang, Jingjing; Liu, Yueyue; Zhang, Qian; Lu, Chao; Tang, Ke; Li, Xiao; Tang, Wei; Gao, Emei; Wu, Can; Dou, Changlin; Hu, Wei
ABSTRACT: Background: Bevacizumab, an inhibitor of angiogenesis, has been approved in several anti-cancer therapies. This study compared the pharmacokinetic (PK) profiles, safety, and immunogenicity of a bevacizumab biosimilar, LY01008, with those of European Union – approved bevacizumab (Avastin®) in healthy Chinese males. Research Design and Methods: In this double-blind, open-label, parallel-group study, healthy Chinese male subjects were randomized 1:1 to receive either LY01008 or Avastin® 3 mg/kg intravenously. Primary study endpoints were PK parameters such as the area under the concentration-time curve (AUC) from time zero to infinity (AUC0–∞ ), AUC from time zero to last quantifiable concentration (AUC0–t ), and maximum serum concentration (Cmax ). Secondary study endpoints included safety, tolerability, and immunogenicity. Results: One hundred and twelve subjects were randomized to receive LY01008 (n = 56) or Avastin® (n = 56). The 90% CIs of the GMRs of AUC0–t, AUC0–∞, and Cmax of LY01008 to Avastin® were all within the bioequivalence margin. Other PK parameters, safety, and immunogenicity profiles were comparable across the two treatment groups. Conclusions: This study demonstrated equivalent PK, comparable safety, and similar immunogenicity of LY01008 to Avastin® in healthy subjects, thus paving the way for further clinical evaluation. Trial Registration: The trial is registered at ClinicalTrials.gov (CT.gov identifier: NCT05110118).